Electromagnetic energy conversion at dipolarization fronts: Multispacecraft results. Issue 6 (9th June 2015) - Huang, S. Y.; Fu, H. S.; Yuan, Z. G.; Zhou, M.; Fu, S.; Deng, X. H.; Sun, W. J.; Pang, Y.; Wang, D. D.; Li, H. M.; Li, H. M.; Yu, X. D.
Abstract: Dipolarization fronts (DFs) are believed to play important roles in transferring plasmas, magnetic fluxes, and energies in the magnetotail. Using the Cluster observations in 2003, electromagnetic energy conversion at the DFs is investigated by case and statistical studies. The case study indicates strongest energy conversion at the DF. The statistical study shows the similar features that the energy of the fields can be significantly transferred to the plasmas (load, J · E > 0) at the DFs. These results are consistent with some recent simulations. Examining the electromagnetic fluctuations at the DFs, we suggest that the wave activities around the lower hybrid frequency may play an important role in the energy dissipation. Key Points: Strongest energy conversion at the DFs Energy of the fields can be significantly transferred to the plasmas Wave activities may play an important role in the energy dissipation